Menelusuri Pola Pemahaman Pemilih Pemula: Perbandingan Antara Pengguna dan Non-Pengguna Media Sosial Twitter dalam Pemilihan Umum 2024 di Kota Serang - Farrir Ilallah; Faiha Zayyan; Dinda Pebriani; Rahmah Nur Sya'bani; Dewi Erlina; Elly Nurlia (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
This research aims to analyze the factors that affect the political participation of novice voters from generation Z in the 2024 General Election. The main focus of the research is to understand the motivation, perceptions, and challenges faced by novice voters in exercising their voting rights for the first time. The research method used is a qualitative approach to phenomenology. The research category includes 4 novice voters who have just participated and become the same experience because of the first time. Data is collected through direct interviews and analyzed using analysis from several predetermined categories. Research results show that there is a comparison of the participation of new voters of generation Z through the use of social media between twitter and non-twitter users supported by the lack of political literacy which has the most significant positive influence on the level of participation.